Performance of Aren Sugar Processors in Wolo District, Kolaka Regency, Southeast Sulawesi - Edi Syah Mihrad; Sitti Aida Adha Taridala; Dasmin Sidu; Weka Widayati; Ine Fausayana; Usman Rianse; Weka Gusmiarty Abdullah; La Ode Jabudin (International Journal of Technology and Education Research, 2025)
This study aims to analyze the performance of palm sugar processors in Wolo District, Kolaka Regency, Southeast Sulawesi. A sample of 60 palm sugar processors was selected using simple random sampling technique from the population in Tolowe Ponrewaru Village and Langgomali Village. Performance data were collected through questionnaires measuring the main activities of sap tapping, sugar processing, and product marketing. Descriptive analysis was used to describe the performance level of processors. The results showed that the performance of processors was in the medium category, with balanced contributions at each stage of the production process. The main constraints found include limited processing technology and access to marketing. These findings provide important implications for increasing productivity and developing the local palm sugar agro-industry.